PEMBELAJARAN BAHASA ARAB BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DI KOTA PADANG - Ritonga, Mahyudin; Nazir, Alwis; Wahyuni, Sri (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
The integration of various fields of sciences and technology is vital in this digital era, including for educational purposes such as the utilization of Information and Communication Technology (ICT) in learning Arabic. However, an obstacle faced by educational institutions is they do not have a clear model in the use of ICT to apply in teaching learning process; therefore, it is an urgent need to conduct a study to find out the best model of ICT-based Arabic learning. This study used qualitative research method covering three stages, i.e. the preliminary, development and implementation phases. The research used purposive sampling and data collection techniques were observation, interviews and documentation. Data analysis technique was the analytical techniques developed by Miles and Hubermas. The result showed that the design of ICT-based Arabic learning model that developed at MTsN Kota Padang is